2016 IEEE/AIAA 35th Digital Avionics Systems Conference (DASC) 2016
DOI: 10.1109/dasc.2016.7778066
|View full text |Cite
|
Sign up to set email alerts
|

Mixed method approach in designing flight decks with touch screens: A framework

Abstract: Abstract-Touch screen technology's first public appearance was in the early 2000s. Touch screens became a part of the daily life with the invention of smartphones and tablets. Now, this technology has the potential to be the next big change in flight deck design. To date, mobile devices are deployed by several air carriers to perform a host of non-safety critical pre-flight and in-flight tasks. Due to high safety requirements requested by authorities, new technologies cannot be adopted as fast as in other sett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…This study is part of a research project that investigates potential benefits and challenges of touchscreens on flight decks. The framework [2] showed that there are many factors (e.g. inflight vibration, location of the display, interface design and interaction strategy) that affect performance.…”
Section: Discussionmentioning
confidence: 99%
“…This study is part of a research project that investigates potential benefits and challenges of touchscreens on flight decks. The framework [2] showed that there are many factors (e.g. inflight vibration, location of the display, interface design and interaction strategy) that affect performance.…”
Section: Discussionmentioning
confidence: 99%
“…Findings from this study and other related studies were used to create a framework [5] showing the relation between various aspects that could impact the usability of touchscreens (fixed and mobile) on the flight deck.…”
Section: Interface Design Guidelinesmentioning
confidence: 99%